Risky Choices – Autonomy and Surveillance in Secondary English Classrooms - Claudia Rozas Gómes (New Zealand Journal of Teachers' Work)
Achievement data from New Zealand secondary schools suggest that students from lower socio-economic communities have fewer opportunities to engage with complex content in subject English. This article examines this phenomenon by drawing on Foucault’s notion of governmentality and considers how a context of simultaneously increased autonomy and surveillance may shape curriculum and assessment choices. To explore these ideas, I use interview data from ten secondary English teachers in the wider Auckland region. I complement Foucault’s (1982) explanation of governmentality with Ball, Maguire, and Braun’s (2012) notion of policy enactment to explore spaces of both compliance and resistance.